An Overview of Strategies for Detecting Genotype-Phenotype Associations Across Ancestrally Diverse Populations - Simonin-Wilmer, Irving; Orozco-del-Pino, Pedro; Bishop, D. Timothy; Iles, Mark M.; Robles-Espinoza, Carla Daniela (Frontiers in Genetics, 2021)
Genome-wide association studies (GWAS) have been very successful at identifying genetic variants influencing a large number of traits. Although the great majority of these studies have been performed in European-descent individuals, it has been recognised that including populations with differing ancestries enhances the potential for identifying causal SNPs due to their differing patterns of linkage disequilibrium. However, when individuals from distinct ethnicities are included in a GWAS, it is necessary to implement a number of control steps to ensure that the identified associations are real genotype-phenotype relationships. In this Review, we discuss the analyses that are required when performing multi-ethnic studies, including methods for determining ancestry at the global and local level for sample exclusion, controlling for ancestry in association testing, and post-GWAS interrogation methods such as genomic control and meta-analysis. We hope that this overview provides a primer for those researchers interested in including distinct populations in their studies.